Significant enhancement of UV emission in ZnO nanorods subject to Ga super(+) ion beam irradiation - Yadian, Boluo; Chen, Rui; Liu, Hai; Sun, Handong; Liu, Qing; Gan, Chee Lip; Kun, Zhou; Zhao, Chunwang; Zhu, Bin; Huang, Yizhong (Nano research, 2015)
Applications of ZnO nanomaterials in optoelectronics are still limited due to their insufficient photoluminescence efficiency. In order to optimize the photoluminescence properties of ZnO nanorods, the UV emission of vertically aligned ZnO nanorods grown on a Si substrate, in correlation with Ga super(+) ion irradiation at different ion energies (0.5 keV-16 keV), was investigated in the present study. We found that the UV intensity increased rapidly with increasing Ga super(+) ion energy, up to its maximum around 2 keV, at which point the intensity was approximately 50 times higher than that produced by as-grown ZnO nanorods. The gentle bombardment of low-energy Ga super(+) ions removes defects from ZnO nanorod surfaces. The Ga super(+) ions, on the other hand, implant into the nanorods, resulting in compressive strain. It is believed that the perfect arrangement of the crystal lattice upon removal of surface defects and the introduction of compressive strain are two factors that contribute to the significant enhancement of UV light generation. [Figure not available: see fulltext.]